Effect of endurance training on dental erosion, caries, and saliva. Issue 3 (11th June 2014) - Frese, C.; Frese, F.; Kuhlmann, S.; Saure, D.; Reljic, D.; Staehle, H. J.; Wolff, D.
<x xml:space="preserve">Abstract</x> The aim of this investigation was to give insights into the impact of endurance training on oral health, with regard to tooth erosion, caries, and salivary parameters. The study included 35 triathletes and 35 non‐exercising controls. The clinical investigation comprised oral examination, assessment of oral status with special regard to caries and erosion, saliva testing during inactivity, and a self‐administered questionnaire about eating, drinking, and oral hygiene behavior. In addition, athletes were asked about their training habits and intake of beverages and sports nutrition. For saliva assessment during exercise, a subsample of n = 15 athletes volunteered in an incremental running field test (IRFT). Athletes showed an increased risk for dental erosion (P = 0.001). No differences were observed with regard to caries prevalence and salivary parameters measured during inactivity between athletes and controls. Among athletes, a significant correlation was found between caries prevalence and the cumulative weekly training time (r = 0.347, P = 0.04). In athletes after IRFT and at maximum workload, saliva flow rates decreased (P = 0.001 stimulated; P = 0.01 unstimulated) and saliva pH increased significantly (P = 0.003). Higher risk for dental erosions, exercise‐dependent caries risk, and load‐dependent changes in saliva parameters point out the need for risk‐adapted preventive dental concepts in the field of sports dentistry.